Education and situation of the plurality of values - Serhii Yosypenko (Філософія освіти, 2020)
According to the author of article, the popularity of the word “values” in scientific and public discourse is due to the logics of how this word is used in the plural, which, in turn, indicates a situation of plurality of values. This article outlines the genealogy of situation of plurality of values ​​on the basis of the works of Jean-Jacques Rousseau, Friedrich Nietzsche, Max Weber. They reflect the different phases of understanding this situation, which appears from the opposition of modern values ​​to traditional values, and European values ​​– the values ​​of other peoples; when Rousseau protests against such opposition, appealing to natural condition of virtue, which doesn’t know such opposition, Nietzsche recognizes the situation of the plurality of values inevitable, because different values correspond to different human inclinations, needs and desires; when  Rousseau considers the spread of science and education to be the cause of a situation of plurality of values, Weber postulates the neutrality of science in relation to the values. The situation of plurality today turns into such problems as the conflict of values, the solution of which is the acceptance of pluralism and in the age of pluralism – the problem of relativization of values. Olivier Reboul, famous French philosopher of education, formulates this problem as a contradiction between the universalist and particularist approach to the European values, which makes education impossible as the transfer of values. On the basis of articulated approaches to this contradiction by Reboul, the author distinguishes the positions of “particularist fundamentalism” and “universalist fundamentalism”. Overcoming this contradiction is possible by rethinking the correlation between particular and universal values, as well as finding universal values that would ensure the unity of separate identities without destroying them. According to the author, in the modern world such values become freedom and science, without which the freedom to choose one's own values is incomplete.